Development and Evaluation of Low Friction Foot Valve - Reddy, K S; Baghde, Harshna D; Varshney, A C; Bhandarkar, D M; Pandey, V K (Journal of Agricultural Engineering, 2007)
Commercial foot valves (CFV) often consume high energy due to improper manufacturing. After testing commercially available foot valves in Bhopal market, a low friction foot valve was designed and developed by replacing the material of construction cast iron by poly propylene (PP) and modifying the flat strainer surface into normal curve surface. The design parameters like the ratios of strainer and flap open areas to suction pipe cross sectional area were kept at recommended values of 3.0 and 1.3, respectively. The low friction foot valve (LFFV) resulted in high discharge (13.66 I/s) over commercial foot valve (11.78 I/s). The average head loss due to friction in LFFV was reduced by 59.4% as compared to CFV with increased velocity head. The friction coefficient of LFVV was estimated as 0.76 (8-16 1/s discharge) meeting the requirements ofBIS (IS: 10805, 1986) as compared to CFV having the friction coefficient of 2.52. The LFFV was found two times energy efficient than CFV, as the additional input power consumption in the former to overcome the head loss was 50% of 110W of the latter. The economic analysis of pumping indicated that the low friction foot valve was economically viable with B: C ratio of2.3:1 with annual net benefit of Rs. 132 .The annual energy saving of 63 kWh in LFFV over CFV was observed with pay back period of 2.4 years.